(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Hormonal replacement therapy (HRT) has been associated with an increased risk of developing breast cancer. The level of risk varies with different types of HRT and the duration of use. Phyllodes tumor accounts for less than 1% of all breast neoplasms and is associated with Li-Fraumeni syndrome. Case presentation: A 37-year-old nulliparous woman presented with a left breast lump. Histological examination revealed a spindle cell neoplasm consistent with a malignant phyllodes tumor. She was diagnosed at age of 12 with ovarian dysgerminoma, had subtotal hysterectomy and right oophorectomy, radiotherapy and chemotherapy. She has been on HRT with conjugated equine estrogens for 13 years and tibolone for the last 5 years. Following the diagnosis of phyllodes tumor, a mastectomy was performed, and HRT was changed to vaginal estrogen gel. Conclusion: Hormonal replacement therapy may pose a risk for certain types of breast cancer, especially with prolonged use of combined therapy. Patients who develop cancers early in life, as well as those on HRT, require close follow-up and adequate patient education with an emphasis on self-breast examination. Sensitization of healthcare providers and patients on the value of genetic screening would facilitate early identification of such patients and follow-up at high-risk clinics.